The Safety of Radiotherapy in the Treatment of Primary Cutaneous B-Cell Lymphoma: A Multidisciplinary Systematic Review - Di Stefani, Alessandro; Tagliaferri, Luca; Lancellotta, Valentina; Fionda, Bruno; Fossati, Barbara; Balducci, Mario; Federico, Francesco; Hohaus, Stefan; De Simone, Clara; Gambacorta, Maria Antonietta; Peris, Ketty (Frontiers in Oncology, 2020)
Primary cutaneous B-cell lymphomas (PCBCL) are rare types of extranodal non-Hodgkin’s lymphoma. The choice of treatment usually depends on the type of PCBCL, the size and location of the involved body surface area as well as patient’s age and health condition. The efficacy of radiotherapy in the treatment of PCBCL has been widely reported although data about the acute and late skin toxicity and patient’s treatment satisfaction and quality of life are scarce. A systematic search using PubMed, Scopus and Cochrane library was performed to identify full original articles analyzing the safety of radiotherapy in patients with PCBCL with the primary outcome to assess the acute and late skin toxicity. Secondary outcomes were complete remission, disease free survival and overall survival. The literature search resulted in 276 articles including 8 studies assessing the safety of radiotherapy for the treatment of PCBCL. Most patients (median 73%, range 11.9%-99.9%) were recorded as having acute skin toxicity of grade 1-2, while acute grade 3-4 toxicity occurred in a median of 8% (range 4-23%) of patients. A median of 20% (range 4%-54%) of patients had late skin toxicity of grade 1-2. No late grade 3-4 toxicity was reported. Only one study evaluated patient’s satisfaction showing that the 97% of patients were satisfied with radiation therapy. This systematic review confirms the safety of radiotherapy in the treatment of PCBCL. Patients with a PCBCL should be managed in highly specialized centers in the context of a multidisciplinary team which includes dermatologist, hematologist, pathologist, and radiation oncologist.